2020
DOI: 10.4103/lungindia.lungindia_204_19
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of InhA and KatG mutations in isoniazid monoresistant Mycobacterium tuberculosis isolates

Abstract: Aims and Objectives: The aim of the study is to detect the pattern of genetic mutation, i.e., Inh A or Kat G or both ( Inh A and kat G) in isoniazid (INH) monoresistant mycobacteria and to correlate with the pattern in multidrug-resistant (MDR) isolates. Materials and Methods: In this study, a quantitative research approach was used. The research design was descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
(21 reference statements)
3
2
0
Order By: Relevance
“…INH mono-resistance forms a major chunk of drug-resistant TB. In our study, resistance to RIF and INH was observed to be 9.6%, while INH monoresistance was found in 6.6% of samples, consistent with previous Indian studies[15][16][17]. The highest resistance to INH was seen in the age groups of 16-35 years.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…INH mono-resistance forms a major chunk of drug-resistant TB. In our study, resistance to RIF and INH was observed to be 9.6%, while INH monoresistance was found in 6.6% of samples, consistent with previous Indian studies[15][16][17]. The highest resistance to INH was seen in the age groups of 16-35 years.…”
supporting
confidence: 91%
“…Although INH resistance is associated with resistance-conferring mutations in multiple genes, katG and inhA account for ~90% of resistance detected by phenotypic DST. INH resistance due to katG gene mutation was documented in 71.9% of INH-resistant study samples, which agrees with previous studies[15,20]. S315T1 mutation was the most common (96.2%) mutation responsible for high-level INH resistance.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…For the inhA gene, the only observed mutation was Mut1, i.e. Cys15Thr, generally associated with an amino acid substitution on codon 15 of the gene [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“… 33 Previous studies have shown that the most common causes of RIF resistance in M.tb are mutations in the katG gene (50–70%) and mabA-inhA promoter region (20–50%). 34 Through WGS, it was determined that the major RIF resistance gene mutations were primarily located in the katG gene (61.11%, 11/18) and fabG1 gene (27.78%, 5/18). All lineages exhibited the katG p.Ser315Thr and fabG1 c.-15C>T mutations, but no mutations were detected in the inhA gene.…”
Section: Discussionmentioning
confidence: 99%